Management of Business Risk in Conditions of Globalization - I. Abuzjarova, Maria (International Journal of Psychosocial Rehabilitation, 2020)
This article reveals the opportunities that are opening in the context of globalization, expansion of world markets, and the accelerated pace of economic, political, and social transformations. The contradictory processes induced by globalization require close study, assessment, and correlation of all benefits and possible threats. The possibility of managing them at various levels of social relations needs to be determined. It is possible to evaluate and look for opportunities to manage globalization processes not only at the global level to reduce risks (threats), but also at the level of countries and their associations, at the level of economic entities, i.e., all sorts of commercial organizations, and at the level of individual activity of people. The research considers the theoretical basis of the effect of the impact on the risk of globalization at derived levels. A systematic scientific approach is needed to define the fundamentals of risk management and understanding globalization processes, since the effects on globalization processes must be balanced and have a long-term positive effect on all levels of social relations, helping to choose optimal development paths that guarantee minimal risks generated by globalization processes.